2016
DOI: 10.7150/jca.16446
|View full text |Cite
|
Sign up to set email alerts
|

Chemomodulatory Potential of Bartogenic Acid Against DMBA/Croton Oil Induced Two-Step Skin Carcinogenesis in Mice

Abstract: Barringtonia racemosa fruits are believed to be useful in cancer treatment in Ayurveda, the Indian system of medicine. In present study, bartogenic acid (BA), a triterpenoid constituent of Barringtonia fruits was evaluated for its cytotoxicity property using the human skin carcinoma cell line (SCC-13) and human peripheral blood mononuclear cells (PBMC). The chemopreventive efficacy of BA was evaluated against the DMBA/Croton oil-induced skin carcinogenesis in mice.BA was orally administered at the doses of 1, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…DMBA, a polycyclic aromatic hydrocarbon has been used to induce irreversible mutation in the cells, [26,27] followed by the repeated application of a tumor-promoter or 12-O-tetradecanoyng agent-phorbol ester phorbol-13-acetate (TPA) is the active constituent from croton oil and it induces accumulation of pro-inflammatory cytokine/chemokines in the skin, which in turn tumor promotion/progression levels. [28][29][30] Hence, in the present investigation, the anticancer activity of CNP was studied individually, and also in combination with CDDP in the DMBA/Croton oil-induced two-step skin carcinogenesis mouse model.…”
Section: Cisplatin (Cis-diamminedichloroplatinum [Cddp]mentioning
confidence: 99%
See 1 more Smart Citation
“…DMBA, a polycyclic aromatic hydrocarbon has been used to induce irreversible mutation in the cells, [26,27] followed by the repeated application of a tumor-promoter or 12-O-tetradecanoyng agent-phorbol ester phorbol-13-acetate (TPA) is the active constituent from croton oil and it induces accumulation of pro-inflammatory cytokine/chemokines in the skin, which in turn tumor promotion/progression levels. [28][29][30] Hence, in the present investigation, the anticancer activity of CNP was studied individually, and also in combination with CDDP in the DMBA/Croton oil-induced two-step skin carcinogenesis mouse model.…”
Section: Cisplatin (Cis-diamminedichloroplatinum [Cddp]mentioning
confidence: 99%
“…DMBA, a polycyclic aromatic hydrocarbon has been used to induce irreversible mutation in the cells, [ 26,27 ] followed by the repeated application of a tumor‐promoter or 12‐O‐tetradecanoyng agent‐phorbol ester phorbol‐13‐acetate (TPA) is the active constituent from croton oil and it induces accumulation of pro‐inflammatory cytokine/chemokines in the skin, which in turn tumor promotion/progression levels. [ 28–30 ]…”
Section: Introductionmentioning
confidence: 99%
“…Extract The SCC13 cells were procured from ATCC (Manassas, VA), and human PBMC was isolated by density centrifugation of heparinized blood of healthy donors using the dextran T-500 sedimentation method (Patil et al 2016). The cells were grown adherently in RPMI-1640 media supplemented with 10% fetal calf serum, 100 U/mL penicillin, and 100 µg/mL streptomycin at 37°C in 5% CO2 with 95% air (Saleem et al 2015).…”
Section: In Vitro Cytotoxic Efficacy Of Cb N-hexanementioning
confidence: 99%
“…[14,15] B. racemosa contains several biologically active phytoconstituents, amongst which bartogenic acid, a natural pentacyclic triterpenoid, is well known for its biological properties, including α-glucosidase inhibitor, anti-arthritic, and anti-cancer. [16][17][18] It has also been reported that various parts of B. racemosa exhibit many pharmacological effects, like anti-oxidant, [14,15,19] anti-inflammatory, [20] anti-fungal, [21] anti-cancer, [22] analgesic, [23] anti-tuberculosis, [24] and anti-diarrhoea activity. [25] To our knowledge, there are no reports on the protective role of B. racemosa or bartogenic acid against anti-cancer drug-induced nephrotoxicity.…”
Section: Abstract a R T I C L E I N F Omentioning
confidence: 99%